A320 WING TRAINING KIT - Sa’adan, Mohd Khairun Nizam; Abu Bakar, Izhar Azreq; J Gukang, Gary Sigar; Venugopal, Mahavishnu; Ghaneson, Thinagaran (Multidisciplinary Applied Research and Innovation, 2021)
Primarily, our idea of the project is an educational tool that provides visual and physical interaction with students in the aviation course. Manufactured with state-of-the-art hardware gives more exposure, discovery and the experience of moving mechanisms. This project can also be implemented in various educational centers to expand the idea of aviation among students and people in general. In other words, our project is aimed to design a wing training kit for students in aviation career as an a tool for education purposes. In addition, this training kit also can reduce costs for (MTO)’s by not spending extra for arranging a study tour on visiting the real aircraft. Compare to other training kit manufacturers, this training kit is the cheapest educational tool that requires minimal cost and maintenance. Purpose for this project is to develop the wing training kit so that the aviation students using this tool could get a better depth in understanding the concept of all sorts of aircraft wings. Next is to demonstrate the the real-life operation on how the wing works which makes the teaching and learning process much easier. An add to that, the scope of our project is subjected to the students taking aircraft maintenance course in Polytechnic Banting and also to students studying aviation courses in other Maintenance Training Organizations (MTO)’s which has a similar exposure. Also, our project is limited to the design of an Airbus A320 aircraft wing only . The last scope of our product is to emphasize the working control surfaces which are flaps, slats, spoilers and aileron